Understanding microplastic presence in different wastewater treatment processes: removal efficiency and source identification - Ma, Min; Huo, Mingxin; Coulon, Frederic; Ali, Mukhtiar; Tang, Zhiwen; Liu, Xin; Ying, Zhian; Wang, Bin; Song, Xin (Elsevier, 2024)
Municipal effluents discharged from wastewater treatment plants (WWTPs) are a considerable source of microplastics in the environment. The dynamic profiles of microplastics in treatment units in WWTPs with different treatment processes remain unclear. This study quantitatively analyzed microplastics in wastewater samples collected from different treatment units in two tertiary treatment plants with distinct processes. The influents contained an average of 15.5 ± 3.5 particles/L and 38.5 ± 2.5 particles/L in the two WWTPs with in the oxidation ditch process and the integrated fixed-film activated sludge process, respectively. Interestingly, microplastic concentrations in the influent were more influenced by the population density in the served area than sewage volume or served population equivalent. Throughout the treatment process, concentrations were reduced to 1.5 ± 0.5 particles/L and 1.0 ± 1.0 particles/L in the final effluents, representing an overall decrease of 90% and 97%, in WWTPs with the oxidation ditch process and integrated fixed-film activated sludge process, respectively. A significant proportion of the microplastics were removed during the primary treatment stage in both WWTPs, with better performance for foam, film, line-shaped and large-sized microplastics. Most microplastics were accumulated in activated sludge, indicating its key role as the primary sink in WWTPs. The multiple correspondence analysis identified laundry washing and daily necessities such as packaging and containers as the major contributors to microplastics in WWTPs. The study proposed recommendations for upgrading WWTPs, modifying designs, and implementing strategies to reduce microplastic sources, aiming to minimize the release of microplastics into the environment. These findings can shed lights on the sources of microplastics in WWTPs, and advance our understanding of the mechanisms for more effective microplastic removals in wastewater treatment technologies in future applications.
Keywords: Microplastics; Population density; Removal; Source apportionment; WWTP upgrade